Sustained censorship in IR (2023-01) (Iran) - Voidly (2023)
CRITICAL severity censorship detected in Iran. Confidence: 75%. Data sourced from OONI.
Censorship Incident ID: IR-2023-0007
Keywords: censorship; IR; censorship; critical